Criminalising bogus hollistic practitioner in the context of criminal law in Malaysia: a study in Shah Alam city / Noorfathana Jaini and Nor Hasnah Omar - Jaini, Noorfathana; Omar, Nor Hasnah (2006)
The belief that there is a connection between faith healing and crime' is certainly not new. The fact that some individuals or groups believe in and are involved in something commonly called faith healing, have to be admitted by the society. One of the reasons is that our societies are really emphasized about the custom and traditions which also consists the matter of supernatural powers. As far as we concern, Malaysia is based on many races that having their own belief and faith and the way of life which include the belief to the invisible creature, that they believe is having power either to be use in good faith or otherwise for example in holistic treatment. ~ Malay race for example, is well-versed with the matter of custom, tradition and way of life that basically belief in the existence of supernatural powers, faith healing or the holistic treatment.